"I will survive": Online streaming and the chart survival of music tracks. (24th August 2020) - Kaimann, Daniel; Tanneberg, Ilka; Cox, Joe
Abstract : Digital streaming has had a profound effect on the commercial music sector and now accounts for 80% of industry revenues in the United States. This study investigates the consumption of music on digital streaming platforms by analyzing the factors affecting the chart survival of individual music tracks. Our data are taken from the Spotify Global Top 200 between January 2017 and January 2020, containing observations on 3, 007 unique tracks by 642 artists over 1, 087 days. We identify a number of unique consumption traits applicable to online streaming services, which we use to explain variations in chart longevity. We find a positive association between the amount of time a track spends in the chart and the involvement of a major label. We also find that the level of competition from other chart entries, as well as some elements related to the pattern of diffusion, associates significantly with the likelihood of chart survival. The study highlights several important managerial implications for key industry stakeholders.